Unusual 4‐arsonoanilinium cationic species in the hydrochloride salt of (4‐aminophenyl)arsonic acid and formed in the reaction of the acid with copper(II) sulfate, copper(II) chloride and cadmium chloride. Issue 4 (1st April 2017) - Smith, Graham; Wermuth, Urs D.
Abstract : The structure of the hydrochloride salt of p ‐arsanilic acid is reported, (I), together with the products from its reaction with copper(II) sulfate, (II), copper(II) chloride, (III), or cadmium chloride, (IV), all featuring the unusual protonated 4‐arsonoanilinium species, viz. in (II), along with the [Cu(H2 O)6 ] 2+ species in a 'double' salt, and as counter‐cation to [CuCl4 ] 2− or [CdCl4 ] 2− in the coordination polymeric sheet structures of isotypic (III) and (IV), respectively. Abstract : Structures having the unusual protonated 4‐arsonoanilinium species, namely in the hydrochloride salt, C6 H9 AsNO3 + ·Cl −, (I), and the complex salts formed from the reaction of (4‐aminophenyl)arsonic acid ( p ‐arsanilic acid) with copper(II) sulfate, i.e. hexaaquacopper(II) bis(4‐arsonoanilinium) disulfate dihydrate, (C6 H9 AsNO3 )2 [Cu(H2 O)6 ](SO4 )2 ·2H2 O, (II), with copper(II) chloride, i.e. poly[bis(4‐arsonoanilinium) [tetra‐μ‐chlorido‐cuprate(II)]], (C6 H9 AsNO3 )2 [CuCl4 ] n, (III), and with cadmium chloride, i.e. poly[bis(4‐arsonoanilinium) [tetra‐μ‐chlorido‐cadmate(II)]], (C6 H9 AsNO3 )2 [CdCl4 ] n, (IV), have been determined. In (II), the two 4‐arsonoanilinium cations are accompanied by [Cu(H2 O)6 ] 2+ cations with sulfate anions. In the isotypic complex salts (III) and (IV), they act as counter‐cations to the [CuCl4 ] 2− n or [CdCl4 ] 2− n anionic polymer sheets, respectively. In (II), the [Cu(H2 O)6 ] 2+ ion sits on a crystallographic centre of symmetry and displays a slightly distorted octahedral coordination geometry. The asymmetric unit for (II) contains, in addition to half the [Cu(H2 O)6 ] 2+ ion, one 4‐arsonoanilinium cation, a sulfate dianion and a solvent water molecule. Extensive O—H…O and N—H…O hydrogen bonds link all the species, giving an overall three‐dimensional structure. In (III), four of the chloride ligands are related by inversion [Cu—Cl = 2.2826 (8) and 2.2990 (9) Å], with the other two sites of the tetragonally distorted octahedral CuCl6 unit occupied by symmetry‐generated Cl‐atom donors [Cu—Cl = 2.9833 (9) Å], forming a two‐dimensional coordination polymer network substructure lying parallel to (001). In the crystal, the polymer layers are linked across [001] by a number of bridging hydrogen bonds involving N—H…Cl interactions from head‐to‐head‐linked As—O—H…O 4‐arsonoanilinium cations. A three‐dimensional network structure is formed. Cd II compound (IV) is isotypic with Cu II complex (III), but with the central CdCl6 complex repeat unit having a more regular M —Cl bond‐length range [2.5232 (12)–2.6931 (10) Å] compared to that in (III). This series of compounds represents the first reported crystal structures having the protonated 4‐arsonoanilinium species.